(untitled) (The South East European Journal of Economics and Business, 2022)
South-East European (SEE) countries are experiencing high emigration, resulting in a significant increase in remittance inflows, exceeding FDI flows. Today the most important challenge facing SEE countries is how to grow at a higher speed to achieve faster economic convergence with the EU. The objective of the paper is to empirically examine the relevance of remittances as a factor of economic growth, using quarterly balanced panel data set of six SEE countries: Albania, Bosnia and Herzegovina, Croatia, Montenegro, the Republic of North Macedonia, and Serbia (SEE6) over 2008q1-2020q2. Panel regression with the fixed-effects model is employed to account for potential cross-section heterogeneity. This study provides original econometric evi- dence that remittances have a significant positive impact on economic growth in our panel of SEE6. Those results will be useful both to scholars and policymakers in the process of the creation of policies that will direct remittances into investments in the economy.